THE MIDDLE-UPPER PALEOZOIC STRATIGRAPHY AND PALEOGEOGRAPHY OF THE TRANSITIONAL AREA BETWEEN THE TURKESTAN OCEAN AND TARIM CONTINENT (TIEN SHAN) - Biske Yu.S.; Dzhenchuraeva A.V.; Neevin A.V.; Vorob'ev T.Yu. (My University, 2003)
New data on the Devonian-Carboniferous stratigraphy in the western part of the Kokshaal-Tau Ridge elucidate geological history of the transitional area between the former Tarim continental shelf in the south and the Turkestan paleoocean in the north. The conodont zonation (additionally substantiated by data on foraminifers, radiolarians and other fossils) is established in the Famennian-Bashkirian sequences of carbonate-clastic deposits of the continental slope and deep-water calcareous-siliceous sediments. The area under consideration was a large (not less than a few hundreds of kilometers wide) pre-collision area of heterogeneous crust. The continental slope (the Kokshaal unit) was bordered in the north by the Aksai pelagic zone with separate volcanogenic and carbonate buildups. In the Middle Paleozoic, the development of carbonate platforms, slopes and bathyal zones was associated for a long time with intraplate basaltic and contrast volcanism. A transgression of the initial Tournaisian time ceased the avalanche sedimentation of material derived from the Tarim continent and triggered a wide development of bituminous sedimentation. In the late Visean-Serpukhovian, it brought about the carbonate deposition in the pelagic zone. Hiatuses in the Middle Carboniferous bathyal sequences represent most likely the sediment dissolution. Fusulinid successions are used to reconstruct more accurately the southward migration of the flysch trough in response to collision of the Tarim margin with the Kazakhstan paleocontinent during the Bashkirian-Late Carboniferous time.
Keywords: Paleozoic; Paleozoic; Палеозой